Prostate cancer arising in ectopic prostatic tissue within the left seminal vesicle: a rare case diagnosed with multi-parametric magnetic resonance imaging and magnetic resonance imaging-transrectal ultrasound fusion biopsy. Issue 1 (December 2016) - Somwaru, Alexander; Alex, Deepu; Zaheer, Atif
Abstract Background Benign ectopia of prostatic glandular tissue in the seminal vesicles is rare with only three prior cases reported in the literature. Prostate cancer, arising within prostatic ectopia in the seminal vesicles, has never been described and therefore presents a challenge in both diagnosis and management. Case presentation Herein, we report a rare case of prostatic adenocarcinoma in ectopic prostate tissue in the left seminal vesicle, without evidence of prostatic glandular involvement. This case was diagnosed on multi-parametric magnetic resonance imaging and confirmed with magnetic resonance imaging-transrectal ultrasound fusion biopsy. Conclusions Awareness of this unusual phenomenon is significant because of the potential occurrence of malignancy to arise in unexpected, extra-glandular locations, which are not routinely sampled on routine transrectal ultrasound biopsy. However attention to lesions with characteristic multi-parametric magnetic resonance imaging features of prostate cancer, regardless of extra-glandular location, will help direct tissue sampling, facilitate a timely diagnosis and ensure appropriate management.